Indispensable : how to become the company that your customers can't live without - Calloway, Joe (John Wiley, 2005)
A five-step strategy for turning a commodity into a necessityWhen products and services become interchangeable, price becomes the ultimate determinant for consumers. Indispensable shows businesses how to break out of that cycle by using The Five Drivers-a strategy that takes companies to the next level of performance.